2007
DOI: 10.1016/j.wasman.2006.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of char derived from various types of solid wastes from the standpoint of fuel recovery and pretreatment before landfilling

Abstract: Carbonization is a kind of pyrolysis process to produce char from organic materials under an inert atmosphere. In this work, chars derived from various solid wastes were characterized from the standpoint of fuel recovery and pretreatment of waste before landfilling. Sixteen kinds of municipal and industrial solid wastes such as residential combustible wastes, non-combustible wastes, bulky wastes, construction and demolition wastes, auto shredder residue, and sludges were carbonized at 500 o C for 1 h under nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 10 publications
2
20
0
1
Order By: Relevance
“…250 to 300 g h -1 of dry SS was loaded to a laboratory-scale rotary kiln-type reactor (φ 0.15 m × 1.2 m) with using a screw feeder and it was pyrolyzed at 500 °C (Hwang et al, 2007). Nitrogen was used as the carrier gas at a rate of 11 l min -1 to maintain an inert atmosphere.…”
Section: Pyrolysis Residuementioning
confidence: 99%
See 2 more Smart Citations
“…250 to 300 g h -1 of dry SS was loaded to a laboratory-scale rotary kiln-type reactor (φ 0.15 m × 1.2 m) with using a screw feeder and it was pyrolyzed at 500 °C (Hwang et al, 2007). Nitrogen was used as the carrier gas at a rate of 11 l min -1 to maintain an inert atmosphere.…”
Section: Pyrolysis Residuementioning
confidence: 99%
“…In contrast, alkali metals tended to be released readily compared to heavy metals. The high acid-buffering pH of incineration ash and the surface properties of pyrolysis residue might be the reasons for the immobilization of heavy metals (Kistler et al, 1987;Inguanzo et al, 2002;Hwang et al, 2007).…”
Section: Weight Reduction By Pyrolysis and Incinerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows the various product yields and qualities obtained by pretreatment. We estimated ASR HHV using HHV data from individual components as listed in (Hwang et al, 2007). By the end of the series of pretreatments, product yield had decreased to 0.5 g g5.6-mm mesh is a simple method to remove ash.…”
Section: Evaluation Of Asr Pretreatmentmentioning
confidence: 99%
“…He et al [24] determined the chemical composition and thermal stability of solid residues, as well as migration and transformation of HMs during SS pyrolysis. Hwang et al [25][26] found that most HMs was completely retained by solid residue after SS pyrolysis treatment and the composition of raw SS had a significant influence on the quality of the resulting residue and thus, the mobility of HMs. Lu et al [27] also studied the influence of pyrolysis temperature on physical and chemical properties of pyrolysis residue.…”
Section: Introductionmentioning
confidence: 99%